FLUKA cross sections for cosmic-ray interactions with the DRAGON2 code. Issue 7 (1st July 2022) - De La Torre Luque, P.; Mazziotta, M.N.; Ferrari, A.; Loparco, F.; Sala, P.R.; Serini, D.
Abstract: Secondary particles produced in spallation reactions of cosmic rays with the interstellar gas provide valuable information that allow us to investigate the injection and transport of charged particles in the Galaxy. A good understanding of the cross sections of production of these particles is crucial to correctly interpret our models, although the existing experimental data is very scarce and uncertain. We have developed a new set of cross sections, both inelastic and inclusive, computed with the FLUKA Monte Carlo nuclear code and tested its compatibility with CR data. Inelastic and inclusive cross sections have been compared to the most up-to-date data and parameterisations finding a general good agreement. Then, these cross sections have been implemented in the DRAGON2 code to characterize the spectra of CR nuclei up to Z = 26 and the secondary-to-primary ratios of B, Be and Li. Interestingly, we find that the FLUKA cross sections allow us to predict an energy-dependence of the B, Be and Li flux ratios which is compatible with AMS-02 data and to reproduce simultaneously these flux ratios with a scaling lower than 20%. Finally, we implement the cross sections of production of gamma rays, calculated with FLUKA, in the Gammasky code and compute diffuse gamma-ray sky maps and the local HI emissivity spectrum, finding a very good agreement with Fermi Large Area Telescope data.